How media narratives can be used in Decision Making under Deep Uncertainty practice? - Molina-Perez, Edmundo; Lempert, Robert J.; Wong, Jody Chin Sing (Frontiers in Climate, 2024)
Media narratives employed in contemporary journalism, including data journalism, are critical in shaping public understanding of the complex systems that affect our lives. Depicting a chain of events in a “story” format, narratives are constructed with detailed, precise, and well-researched information based on character identification, human emotions, and real social problems. In many ways, they are indispensable intermediaries of practiced judgment and expertise that guide the public to meaningfully engage with evidence-based understanding of our world and how we can act upon it. DMDU narratives suggest that we can act to shape the future toward our liking even when we cannot predict what that future will be, that we need to simultaneously consider multiple rather than a single future, and that the quest for prediction can interfere with the task of identifying the best actions. DMDU practice relies on substantive stakeholder interaction, and it is supported by vast amounts of empirical evidence. This perspective discusses how media narratives intersect with DMDU to inform and to leverage the complexities of modern contemporary public challenges. We first explore how uncertainty might be actionable, as opposed to fearful. Next, while acknowledging limitations on transference of information during the journalistic process, we address the challenges and best strategies to distill information to the public to maintain and build trust about uncertainty. Next, we discuss how journalistic practices could be useful for disseminating more broadly findings of DMDU analyses.